Pharmacokinetics of vancomycin in critically ill patients in Thailand - Thitinat Dedkaew (2018)
© 2015, International Journal of Pharmacy and Pharmaceutical Science. All rights reserved. Objective: The pharmacokinetics and pharmacodynamics of drugs in critically ill patients are difficult to predict due to complex pathophysiological changes. Vancomycin is an antibiotic commonly used to treat serious gram positive bacterial infections in critically ill patients and the treatment goal is to rapidly achieve and maintain therapeutic concentrations. We assessed the pharmacokinetics of vancomycin in critically ill patients to help guide dosing. Methods: A total of 138 patients with 299 vancomycin serum concentrations were included in this analysis. Vancomycin serum concentrations were measured using a fluorescence polarization immunoassay. Population pharmacokinetic parameters were estimated using nonlinear mixed effects regression. Age, creatinine clearance (CrCL) and body weight were tested as potential covariates in the pharmacokinetic model. Results: Vancomycin concentration-time profiles were best described by a two-compartment pharmacokinetic model with an additive error model for between subject variability. Creatinine clearance significantly influenced vancomycin clearance (CL). Mean population pharmacokinetic parameters (% between subject variability) were: CL 3.39 l/h (13%), central compartment volume of distribution (V1) 24.92 l (26%); and peripheral compartment volume of distribution (V2) 24.6 (37%). Conclusion: Higher clearance and a smaller volume of distribution of vancomycin was observed in critically-ill patients compared to those reported in non-critically ill patients with a similar distribution of renal function and body weight. Close monitoring of vancomycin serum concentrations is warranted in critically ill patients with dose interval adjustments based on the patient’s creatinine clearance.